A Review: Haemonchus contortus Infection in Pasture-Based Sheep Production Systems, with a Focus on the Pathogenesis of Anaemia and Changes in Haematological Parameters - Kate J. Flay; Fraser I. Hill; Daniela Hernandez Muguiro (Animals, 2022)
Haemonchosis is an important cause of anaemia in sheep worldwide, particularly those that are kept in pasture-based systems in warm, high rainfall environments. Potential outcomes vary based on the severity of infection and the sheep’s immune response, however, in some sheep infection can lead to death. The consequences of Haemonchus contortus infection mean that it has been well-studied in a range of different farming systems. However, to our knowledge, there has not been a recent review focused on the pathophysiology of anaemia caused by haemonchosis. Thus, this review provides an in-depth discussion of the literature related to the pathophysiology of haemonchosis and associated clinical signs for hyperacute, acute, and chronic haemonchosis. Additionally, haematological and biochemical findings are presented, and various diagnostic methods are assessed.